Activating farmers : uses of entrepreneurship discourse in the rhetoric of policy implementers - Pyysiäinen, Jarkko; Vesala, Kari Mikko (Sage, 2013)
Research on entrepreneurship as a policy discourse has focused mostly on relations between the discourse and targets of the policy, that is, actors intended to become entrepreneurial or entrepreneurs, while the role of policy implementers has received much less attention. The present study examines the ‘rationality’ of entrepreneurship policies by analyzing how actors in charge of the grassroots level policy implementation in the farming context use entrepreneurshipdiscourse and argue for the communicative and interactive viability of their mission. The analysis of stances and positioning in interview talk reveals that policy implementers are active discourse users who, on the one hand, are able to reflect on the dilemmas and problems inherent in their task but, on the other hand, use their rhetorical agency to maintain and defend their mission as promoters of entrepreneurship policy and to save and support their own face as experts. As a result, the implementation emerges as a delicately managed interaction process.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; agency; entrepreneurial governance; expertise; implementation; rhetorical social psychology; maatalousyrittäjät; farming; entrepreneurship; yrittäjyys; retoriikka